Assessing university students' perceptions of their Physics instructors' TPACK development in two contexts. (29th July 2014) - Chang, Yahui; Jang, Syh‐Jong; Chen, Yang‐Hsueh
Abstract: Technological Pedagogical and Content Knowledge (TPACK) has been gaining traction among educational researchers; however, studies documenting university students' perceptions of their teachers' TPACK remain limited. This study intends to investigate the professional development of two physics instructors through the lens of the TPACK framework. Moreover, this study spans an 18‐week semester within both the contexts of Taiwan and China. Multiple data were collected and analyzed, including the pretest and posttest TPACK surveys, instructor interviews, in‐class observations and students' feedback and opinions. The results revealed that John's instructional representations and strategies and technology integration and application scores increased significantly, as well as Mike's knowledge of students' understanding score showing a significant increase from the middle to the end of semester. John (Taiwan) emphasized life examples and the use of multimedia while Mike (China) chose to emphasize students' knowledge and evaluation. Such results showed different teaching characteristics in the two contexts. Implications and suggestions are put forward based on the results of this study.